Processing and Conversion of Oil and Gas: Modeling, Control, Simulation and Optimization - Assaf, Jean-Claude (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Processing and Conversion of Oil and Gas: Modeling, Control, Simulation, and Optimization describes the core of the activity of petrochemical engineers, process controller engineers, industrial engineers, energy engineers, and researchers in the oil and gas field. This reprint explores the modeling, control, simulation, and optimization of new and revamped petrochemical processes using proven software. Thus, it offers novel illustrative examples, prospective applications, and solutions to improve these processes. This reprint aims to combine theoretical principles with examples modeled by commonly used simulation software employing steady-state or dynamic process simulation. Furthermore, applying numerical methods and optimization at both the theoretical and practical levels is within the scope of this reprint.